(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Structured Aquatic Training Program was designed to test Children with Special Need (CWSN) touch processing, in which 25 children aged range of 7 -11 years with sensory needs children were purposely selected for the study and was divided into Experimental group and Control group. The data was collected from a special school at Delhi, India and statistically analyzed by employing two-way ANOVA. Findings indicate towards no accelerated change within the stipulated duration of the training, and directs towards contentious tough intervention for long term benefits. The scores obtained in touch processing also indicate some changes in the scores of questionnaire, with this it can be assumed that, may be longer duration of intervention will give better results.